The Effect of Working Capital Turnover, Capital Structure, and Liquidity on Profitability in Hotel and Restaurant Companies Listed on The Indonesian Stock Exchange - Pradnyana, I Made Ardi; Widnyana, I Wayan; Tahu, Gregorius Paulus (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of working capital turnover, capital structure, and liquidity on profitability in hotel and restaurant companies listed on the Indonesia Stock Exchange during the period 2021-2023. The research method used is multiple linear regression analysis with secondary data taken from company financial reports. The results show that working capital turnover has a positive and significant effect on profitability, indicating that efficient working capital management can improve a company's ability to generate profits. On the other hand, capital structure has an insignificant negative effect on profitability, indicating that high debt levels do not always lead to increased company profits. Meanwhile, liquidity was found to have a positive and significant effect on profitability, emphasizing the importance of a company's ability to meet its short-term obligations in improving its financial performance. This study is expected to provide insights for company management in managing working capital, capital structure, and liquidity to achieve optimal profitability.